A Quantitative Analysis of Recruitment Strategies and Their Impact on Employee Engagement - Hu, Xiao (Pacific International Journal, 2024)
Recruiting and selecting talent is crucial for building a high-performing workforce, directly impacting employee engagement and organizational performance. This study examines the relationship between recruitment strategies and employee engagement in Shenzhen-based companies, focusing on Huawei Technologies Co., Ltd. and Tencent Holdings Limited. Through a quantitative analysis involving 200 staff members, the study explores patterns, trends, and correlations to uncover the dynamics between recruitment strategies and employee engagement. The findings reveal strengths and areas for improvement in recruitment practices, emphasizing the need for alignment with organizational goals, transparency, and innovation. Furthermore, the study highlights the critical role of employee engagement in driving productivity, job satisfaction, and organizational success. Recommendations are provided to enhance transparency in recruitment processes, invest in comprehensive onboarding programs, foster diversity and inclusion, strengthen cross-departmental collaboration, prioritize employee well-being, and solicit feedback for continuous improvement.